Human plasma kallikrein: roles in coagulation, fibrinolysis, inflammation pathways, and beyond - Motta, Guacyara; Juliano, Luiz; Chagas, Jair Ribeiro (Frontiers in Physiology, 2023)
Human plasma kallikrein (PKa) derives from activating its precursor, prekallikrein (PK), historically named the Fletcher factor. PKa and tissue kallikreins are serine proteases from the same family, having high and low molecular weight kininogens (HK and LK) as substrates, releasing bradykinin (Bk) and Lys-bradykinin (Lys-Bk), respectively. This review presents a brief history of PKa with details and recent observations of its evolution among the vertebrate coagulation proteins, including the relations with Factor XI. We explored the role of Factor XII in activating the plasma kallikrein-kinin system (KKS), the mechanism of activity and control in the KKS, and the function of HK on contact activation proteins on cell membranes. The role of PKa in cell biology regarding the contact system and KKS, particularly the endothelial cells, and neutrophils, in inflammatory processes and infectious diseases was also approached. We examined the natural plasma protein inhibitors, including a detailed survey of PKa inhibitors' development and their potential market.